The Sabbatean syndrome, the messianic idea and Zionism - CHARVIT, YOSSEF (2024)
My research, still in its early stages, proposes a basic methodological and historiographic perspective that transcends particularistic analysis. This perspective challenges the crisis orientation that has dominated Zionist historiography and examines the roots of Zionism that are integral to the Sephardic diaspora. The purpose, conscious or otherwise, of Zionist historiography that detaches the sixteenth from the nineteenth century is to ensure that the mighty process of return to the Jewish homeland is attributed exclusively to Zionism of the modern era. This ignores all the momentous accomplishments of the sixteenth century that heralded a new age in the settlement of Eretz Israel. Most Zionist historiographers attempt to ‘normalize’ history so that anything hinting at redemption is summarily excised. This is the meaning of the historiographic dispute taking place over the past few decades concerning messianism and the history of Jewish settlement of Eretz Israel in the modern era.
Keywords: Early Modern Period; Israel; Messianism; Modern period; Sabbatianism; Sephardim; Zionism; Diaspora; Historiography